Initial oxidation of Ni3Al - Singer, Patrick (My University, 2009)
The properties of a thin oxide layer grown on top of an alloy can vary from those of the bulk material. Therefore, a grown oxide film can alter the properties of the solid like thermal and electronic conductivity, friction and wear resistance, and adhesion. Throughout the last decades, the growth mechanisms of oxide films on top of alloys have been in the scientific and technological focus. Thereby, new fields of applications of these alloy-oxide systems were developed i.a. microelectronic devices, coating systems, and catalytic systems. Further extensive knowledge of the initial stages of the oxidation of alloys could lead to new developments in the future. In this work the initial stages of oxidation of a single-crystalline Ni3Al alloy with a (111) surface orientation were investigated at various temperatures at an oxygen partial pressure pO2 = 1 x 10-6 mbar. A combination of surface-sensitive techniques (real-time in-situ ellipsometry (RISE), angle-resolved X-ray photoelectron spectroscopy (AR-XPS), low electron energy diffraction (LEED), and scanning tunneling microscopy (STM)) were applied to investigate the growth kinetics, the composition, and the morphology of the growing oxide film. Furthermore, in-situ X-ray diffraction studies were carried out to investigate the atomic composition of the clean Ni3Al surface and the oxidation-induced changes in the alloy microstructure at the alloy-oxide interface at the synchrotron light source Angströmquelle Karlsruhe (ANKA). First, a reproducible cleaning procedure of the Ni3Al (111) surface has been defined to obtain a clean and chemically ordered surface. A long annealing step at sufficiently high temperatures is required to restore the composition and surface structure after sputtering. The thus obtained Ni3Al (111) surface gives a sharp LEED pattern with a (2x2) surface structure. STM indicates that the cleaned alloy surface is atomically flat. The oxide-film growth kinetics on a Ni3Al (111) surface at T ≤ 500 K can be subdivided into two stages. The growth rate of the oxide-film is very fast at the onset of oxidation. A second growth regime follows for which the growth rate levels off. After t = 6000 s, it becomes negligibly small and a near-limiting oxide-film thickness is reached. At T ≥ 600 K, no near-limiting thickness of the oxide layer is observed. The transition from the initial to the second growth regime is more gradual. Aluminum is oxidized preferentially at the onset of the oxidation. Due to the high amount of Ni within the Ni3Al (111) surface layers and the kinetically hindered Al segregation from the bulk towards the oxidizing surface, nickel oxide is formed upon oxidation also. The grown oxide layer consists of both nickel oxide and aluminum oxide. Induced by the oxidation defects are formed in the alloy lattice at the alloy-oxide interface additionally. It could be shown that nickel antisite atoms are formed in the second atomic layer at oxidation temperatures of T = 600 K. This thesis presents the initial stages of oxidation of a Ni3Al (111) surface. New scientific findings of the kinetics and the composition of the formed oxide-film contribute to the basic understanding of the oxidation behavior of alloys, particularly of Ni3Al. These findings enable new and/or further technological developments of alloy-oxide systems. The presented results of the alloy surface composition of the clean surface and at the alloy-oxide interface reveal a further part of fundamental research for the Al-Ni system.
Keywords: Materialteknik; Konstruktionsmaterial; Teknisk fysik; Materialfysik med ytfysik; Materials Engineering; Construction materials; Engineering physics; Material physics with surface physics